THE INFLUENCE OF TOTAL QUALITY MANAGEMENT AND SUPPLY CHAIN MANAGEMENT ON THE OPERATIONAL PERFORMANCE OF USED CAR SHOWROOMS IN PEKANBARU: THE ROLE OF COMPETITIVE ADVANTAGE AS A MEDIATING VARIABLE - Kumala, Evidya; Nugroho, Gilang; Lubis, Rehansa (Jurnal Apresiasi Ekonomi, 2026)
This study aims to analyze the effect of Total Quality Management (TQM) and Supply Chain Management (SCM) on organizational performance (OP) with competitive advantage as a mediating variable in used car showrooms in Pekanbaru. Using a Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) approach, this study tests five main hypotheses that link these constructs. The results of the hypothesis testing show that competitive advantage plays an important role in improving organizational performance, while TQM and SCM are proven to have a significant influence on competitive advantage. SCM and CA significantly improve organizational performance, while TQM does not show a significant direct influence on organizational performance or competitive advantage. This study provides important insights for used car showrooms in Pekanbaru to utilize TQM and SCM in designing more efficient operational strategies and improving competitive advantage to face increasingly fierce competition. These findings also contribute to the literature on quality management and supply chain in the Indonesian automotive industry, as well as providing practical directions for improving company performance and competitiveness